Shear Bond Strength of Zirconia Ceramic to Four Different Core Materials, An in vitro Study - Sara Tavakolizadeh; Mohamad Dehghan; Rahab Ghoveizi; Anahita Fayyazi (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Different materials can be used to reconstruct the core foundation in all-ceramic restorations. Bond strength of the core material to zirconia is an important factor in long-term restoration success. Purpose: The aim of this study was to assess shear bond strength (SBS) of zirconia to four different core materials. Materials and Method: In this experimental in vitro study, 40 zirconia ceramic disks (10×3 mm) were prepared and divided to four groups based on core material. Cylinder shaped core specimens (3×4 mm) of non-precious gold alloy (NPG), zirconia ceramic, natural dentin, and composite resin were prepared and bonded perpendicularly to the zirconia disks using Gillmore Needle Apparatus and dual cure resin cement. All samples were thermocycled for 2000 cycles. To evaluate SBS, the specimens were tested by universal testing machine. Data were analyzed using Kruskal-Wallis test followed by Dunn's test with Bonferroni correction. Statistical significance was set at p< 0.05. Results: The highest values for SBS were achieved in composite resin group (11.58±1.74 MPa) followed by NPG (10.32±0.94 MPa), zirconia (7.3±1.11 MPa) and dentin group (6.53±0.56 MPa). SBS in composite resin and NPG core materials were significantly higher than other core materials (p< 0.05). Conclusion: Composite resin and NPG cores showed significant higher bond strength to zirconia in comparison to dentine and zirconia core materials.